2008
DOI: 10.1111/j.1742-4658.2008.06505.x
|View full text |Cite
|
Sign up to set email alerts
|

An internal ribosome entry site mediates the initiation of soluble guanylyl cyclase β2 mRNA translation

Abstract: The soluble guanylyl cyclases (sGC), the receptor for nitric oxide, are heterodimers consisting of an α‐ and β‐subunit. This study aimed to investigate the translational mechanism of the sGC β2‐subunit. Two mRNA species for sGC β2 were isolated from human kidney. These transcripts had dissimilar 5′‐untranslated regions (5′‐UTRs). The most abundant sGC β2 mRNA showed numerous upstream open reading frames (ORFs) and stable secondary structures that inhibited in vivo and in vitro translation. To evaluate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Each subunit has two isoforms, α1 α2 β1 β2, yet the sGCα1β1 is the most abundant whereas the sGCα2β1 is more predominant in brain tissue [11]. The precise role for β2 subunit is not fully understood and it could have a dominant negative regulatory role [12]. The subunit arrangement for sGCβ1 includes the above mentioned C-terminal CC and GC domains as well as an N-terminal NO-sensing H-NOX/H-NOB and adjacent H-NOXA/H-NOBA/PAS domains.…”
Section: Introductionmentioning
confidence: 99%
“…Each subunit has two isoforms, α1 α2 β1 β2, yet the sGCα1β1 is the most abundant whereas the sGCα2β1 is more predominant in brain tissue [11]. The precise role for β2 subunit is not fully understood and it could have a dominant negative regulatory role [12]. The subunit arrangement for sGCβ1 includes the above mentioned C-terminal CC and GC domains as well as an N-terminal NO-sensing H-NOX/H-NOB and adjacent H-NOXA/H-NOBA/PAS domains.…”
Section: Introductionmentioning
confidence: 99%
“…However, the highly folded 5′‐UTR secondary structure might behave as cap‐independent internal ribosome entry site (IRES). The translation efficiency via IRES‐mediated mechanisms found in some viruses [Jackson, 1988; Lourenco et al, 2008] and eukaryotic mRNAs [Hellen and Sarnow, 2001; Vazquez‐Padron et al, 2008] has been known, as the 5′‐UTR sequences contain GC‐rich and complex secondary structures. Except for the likely heat‐activated IRES of that of Drosophila Hsp90 [Ahmed and Duncan, 2004], no IRES structure has so far been described in the 5′‐UTR sequences of rat Hsp90 isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Several β2 splice variants have been described in the literature [17, 18, 81, 92]. The human canonical RefSeq gene is comprised of 17 exons (NR_003923) and surprisingly is listed as a non-coding RNA.…”
Section: Regulation Of Sgc Expressionmentioning
confidence: 99%
“…Finally, in a recent report, a new splice variant encoding an ORF with additional amino acids at the N-terminus was described [92]. Interestingly, the same report demonstrated that 5'UTRs of the two alternative β2 sGC transcripts (`canonical' and new splice form) possess an active internal ribosome entry site (IRES).…”
Section: Regulation Of Sgc Expressionmentioning
confidence: 99%